Pemberdayaan PRA Tamantirto Utara melalui Pelatihan Pembuatan Es Krim Jamu dan Sosialisasi DAGUSIBU serta Pemeriksaan Kesehatan: PRA Tamantirto Empowerment through Herbal Ice Cream Making Training and DAGUSIBU Socialization and Health Checks - Muhammad Fariez Kurniawan; Revitha Nova Salsabila; Raif Umbara; Lisanda Dwi Adriani; Kartini Faray; Adel Zilvia Natasha; Rifatun Nisa; Fatma Novia; Siti Sarah; Hasna Raidatus Syida; Dyah Wikansih; Intan Yuriska; Najmuddin Dzulfikar Al Amru; Ingenida Hadning; Mia Audita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Pimpinan Ranting Aisyiyah (PRA) Tamantirto Utara is part of the Muhammadiyah association. Universitas Muhammadiyah Yogyakarta (UMY), especially the Pharmacist Professional Education Study Program has the responsibility to carry out the guidance and empowerment of PRA. The purpose of this community service activity is to empower PRA Tamantirto Utara in the introduction of health products in the form of training in making herbal ice cream and improving health status through DAGUSIBU (Get, Use, Save and Dispose of) medicine and health checks. This activity is in collaboration with the student hermitage of the UMY Pharmacist Professional Education Study Program. The method used in this activity is through training in making herbal ice cream, DAGUSIBU counseling, health checks (cholesterol checks, blood sugar and uric acid) which ends with the provision of equipment grants. The activity begins with a pretest and ends with a posttest to evaluate the participants' understanding. The management of the PRA Tamantirto Utara received knowledge of herbal medicine processing into ice cream preparations, as well as a comprehensive understanding of DAGUSIBU as evidenced by an increase in the pretest score of 88.57% to 97.62%. The results of the examination showed that only about 19.04% had hypercholesterolemia, 9.52% had hyperglycemia, and 14.28% had hyperuricemia. Education on the handling of metabolic disorders was given to the PRA Tamantirto Utara. This community service activity provides skills and insight into making herbal ice cream, understanding DAGUSIBU and efforts to improve health status for PRA Tamantirto Utara.